Petrogenesis of the recent trachytic pyroclastic succession of Agua de Pau Volcano, (Sao Miguel, Azores) - Storey, Michael (2018)
International Symposium on the Activity of Oceanic Volcanoes. Ponta Delgada, 4-9 August 1980.